Combining nanotechnology with the multifunctional roles of neutrophils against cancer and inflammatory disease. Issue 5 (26th January 2022) - Tang, Lu; He, Shun; Yin, Yue; Li, Jing; Xiao, Qiaqia; Wang, Ruotong; Gao, Lijun; Wang, Wei
Abstract : This review highlights the recent achievements of combining nanomaterials with neutrophil-based delivery systems against cancer and inflammatory disease, and also emphasizes the key role of neutrophils in the progression of various diseases. Abstract : Neutrophils, the most abundant leukocytes in humans, play a crucial role in acute inflammation during infection and tumorigenesis. Neutrophils are the major types of cells recruited to the inflammation sites induced by pathogens, exhibiting great homing ability towards inflammatory disorders and tumor sites. Therefore, a neutrophil-based drug delivery system (NDDS) has become a promising platform for anti-cancer and anti-inflammatory treatment. Recent decades have witnessed the huge progress of applying nanomaterials in drug delivery. Nanomaterials are regarded as innovative components to enrich the field of neutrophil-based therapies due to their unique physiochemical characteristics. In this review, the latest advancement of combining diverse nanomaterials with an NDDS for cancer and inflammatory disease treatment will be summarized. It is discussed how nanomaterials empower the therapeutic area of an NDDS and how an NDDS circumvents the limitations of nanomaterials. Moreover, based on the finding that neutrophils are closely involved in the progression of cancer and inflammatory diseases, emerging therapeutic strategies that target neutrophils will be outlined. Finally, as neutrophils were demonstrated to play a central role in the immunopathology of COVID-19, which causes necroinflammation that is responsible for the cytokine storm and sepsis during coronavirus infections, novel therapeutic approaches that anchor neutrophils against the pathological consequences related to COVID-19 will be highlighted as well.